Population and hunger in the world: agriculture, food, development. - Postiglione, Luigi (Medicina e Morale, 2004)
Agricolture provides food for nutrition, and it is one of the most important factors of the equilibrium of the agricultural eco-system, being the engine thrust of progress. Yet, 4/5 of the growing population of the world lacks food, mostly due to an inadequate distribution of agricultural products. Whilst a considerable amount is currently destroyed in the most developed countries to support speculation in the market strategies. In the XX century, in fact, the availability of food has shown a tangible increase in the areas of production and are now 4-5 times the former averages, and the production of soils previously uncultivable is now given to the quality of products. But such an increase is due to technological innovation and the use of fertilizers and fito-pharmaceuticals which have caused pollution and an excessive consumption of fossil-generated energy. An alternative opportunity of increasing agricultural production aimed at protecting the environment, would require a correct application of technical instruments together with the use of more traditional agricultural methods which would gain new meaning. Nonetheless, the protection of soil and monitoring of the emission of carboni- anhydride into the atmosphere are further means of improving the agricultural- ecosystem. These objectives are largely achieved by the most industrialized countries, but are to be reached by the underdeveloped emerging portions of the world, by assuring a meaningful partecipation of local experts and authorities, and by offering valuable development programs, which show precise knowledge of the environmental characteristics of each area and of their social and cultural backgrounds and pedoclimatic conditions. The author has examined the technological and scientific aspects related to each subject treated, and concludes with a surprising note of optimism, generated by his many years of experience as an agronomist and by his empiric knowledge of the potential productivity of all the areas in the world, and also based on the work of other fellow researchers. It is the author's conviction that agriculture is fully capable of providing nutrition for the entire Planet, if only the selfishness of certain nations is overcome, and that it will be even when in 2030 the world's population is predicted to be: 8.270.000.000.